PENERAPAN METODE TURUTAN PEMBELAJARAN AL-QUR’AN ANAK USIA DINI DI TPQ ASSALAM BELIK - Mutohharoh; Sabrina Anindya Khamsa; Tifani Zulfi Nadia; Zaviana Dwi Safitri; Sutrimo Purnomo (TSURAYYA: Journal Education, Economy and Religia, 2026)
Qur'an learning for early childhood requires methods that are in accordance with the characteristics of child development, which tend to need a gradual, repetitive, and enjoyable learning process, yet in practice, less than optimal learning is still found. This study aims to explore the implementation of the sequential method in Qur'an learning for early childhood at TPQ Assalam Belik, Pemalang, as well as to identify its effectiveness in improving reading skills and instilling religious character. This study uses a qualitative approach with a case study design, with research subjects including educators, students, and institution managers. Data were collected through observation, interviews, and documentation, and then analyzed using interactive analysis techniques, which include data reduction, data presentation, and drawing conclusions. The results of the study indicate that the sequential method is applied in stages, starting from the introduction of hijaiyah letters, pronunciation exercises, up to reading simple Qur’an, and is considered effective because it suits the learning needs of early childhood. This method not only improves reading skills but also supports the formation of religious attitudes through habituation of religious values, with a high level of student involvement, thereby creating an interactive and enjoyable learning atmosphere. However, there are obstacles such as limited facilities, suboptimal learning planning, and lack of family support. Thus, the sequential method can be an effective approach in early childhood Qur’an learning, provided there is optimal support from educators, facilities, and parental involvement.